2022
DOI: 10.1590/s1984-29612022040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and parasitological impact of short-term treatment using miltefosine and allopurinol monotherapy or combination therapy in canine visceral leishmaniasis

Abstract: Canine visceral leishmaniasis is an endemic zoonosis in Brazil. Dogs are the main hosts in urban environments. The treatment has gained popularity since the Brazilian government authorized miltefosine for canine treatment. The aim of this study was to investigate the clinical and parasitological impact of short-term treatment with miltefosine and allopurinol, alone and in combination. We evaluated the ability of pharmacotherapy to reduce clinical signs of disease, antibody levels using the indirect fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Studies have demonstrated a good clinical response in dogs naturally infected by L. infantum and treated with miltefosine alone or in combination with other drugs [11,13,14,19,20]. Our results showed that associating Milteforan ® with the continuous use of allopurinol contributes to controlling clinical signs of the disease.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Studies have demonstrated a good clinical response in dogs naturally infected by L. infantum and treated with miltefosine alone or in combination with other drugs [11,13,14,19,20]. Our results showed that associating Milteforan ® with the continuous use of allopurinol contributes to controlling clinical signs of the disease.…”
Section: Discussionsupporting
confidence: 51%
“…Ramos et al (2023) [19] also observed a decrease, without significance, in antibody titers three months after treatment with miltefosine. Ayres et al (2022) [14] did not observe a reduction in antibody titers, but the evaluation was carried out 28 days after treatment with miltefosine and allopurinol. According to Paltrinieri et al (2016) [31], a decrease in antibody titers is expected six months after treatment, but in dogs living in endemic areas, the complete clearance of antibodies is unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the relevant data extracted from each of the 16 selected articles and the analysis of the different studies. In total, these studies included the evaluation of 598 dogs diagnosed with leishmaniosis; 15 dogs were subtracted from the total as they were shared in two publications [12,13]. Strength of evidence.Meta-analyses or systematic reviews [10]; Randomized controlled trials [11]; Cohort studies, non-randomized controlled trials [12,13];Case/control studies [7,14]; Case series, case reports [6,[15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Despite its efficacy, the use of miltefosine in monotherapy is not recommended due to a higher risk of therapeutic failure [ 15 ] or recurrences after the interruption of treatment [ 16 , 17 ]. Instead, the combined therapy of miltefosine and leishmaniostatic allopurinol is a protocol of documented efficacy [ 18 , 19 ] and is considered among those the first choice for CanL therapy [ 4 , 20 ]. Nevertheless, the Miltefosine-Allopurinol (MIL-AL) protocol is sometimes considered a second-choice treatment when compared to meglumine-antimoniate—allopurinol combination, mainly for the risk of earlier relapses [ 21 , 22 ] or the development of parasite drug resistance [ 23 ].…”
Section: Introductionmentioning
confidence: 99%